TECHNOLOGIES AND TRADITIONS: BARRIERS ON THE PATH TO DIGITALIZATION IN HIGHER EDUCATION (Scientific Journal of the Dragomanov Ukrainian State University Series 2 Computer-Oriented Learning Systems, 2025)
The article provides a comprehensive analysis of the digitalization processes in higher education, with a focus on preserving academic traditions. The main advantages of digital technologies in the educational process are considered: flexibility of educational trajectories, increased accessibility of knowledge, the possibility of personalized learning, automation of assessment, and support for inclusive education. At the same time, a few obstacles to the digital transformation of universities are identified: resistance to changes from teachers and administration, an insufficient level of digital literacy among teachers and students, psychological barriers, technical difficulties, financial constraints, and ethical challenges associated with maintaining academic integrity and reducing the quality of interpersonal interaction. Special attention is paid to the philosophical, socio-cultural, and pedagogical foundations of the traditional model of education. The value of the academic heritage, which has been formed over the centuries and plays a crucial role in shaping personality and preserving the identity of the university environment, is meaningfully considered. A comparative analysis of educational approaches in different regions of the world – in particular, European, American, and Asian models – was conducted to clarify the degree of influence of digital technologies on national educational traditions. Differences in the perception of education as a social institution in different cultures were revealed, as well as the role of digitalization in the transformation of classical pedagogical paradigms. The authors emphasize that the introduction of digital technologies should not only consider the cultural and historical features of the educational environment but also preserve the key principles of the humanistic approach to learning. The article also proposes the introduction of hybrid learning as an effective balance between traditional and innovative approaches, the development of digital competencies of participants in the educational process, and the formation of a state policy to support digital transformation.
Keywords: digitalization of education; higher education; digital literacy; academic integrity; barriers; innovation; ethics; psychological challenges; ICT in education